Artificial Intelligence in ECG interpretation - review article - Łukasz Fussek; Jagoda Niewiadomska; Borys Bondos; Aleksandra Stępień; Alicja Paluch; Jakub Skrzypek; Aleksandra Język Polski; Robert Kochan; Ewelina Wieczorek; Kacper Lee (Journal of Education, Health and Sport)
Introduction and purpose